NILAI EKONOMI KONSERVASI SAUJANA BUDAYA KAWASAN BOROBUDUR Sebuah Eksperimen Pilihan - Amiluhur Soeroso (Journal of Indonesian Economy and Business (JIEB), 2007)
The values of Borobudur cultural landscape has conferred important meaningsin many aspects for those who live in its surrounding area. However, its culturallandscape (natural and cultural horizon) is constantly facing of degrading quality whichaffecting the future existence of Borobudur’s site.This research aims to explore and monetarily quantify the benefit of Borobudurcultural landscape to support the conservation efforts using choice experimentframework. Data were obtained from sample visitors and structured questionnaire arechosen for assessment of economic benefit using choice experiment, an “expressedpreferences” method to assess the total economic benefit of conservation zone.The results indicate that the total economic benefit of Borobudur area is veryhigh. Consequently, the public loss, which is caused by poor management policy, will bevery high in financial term. Therefore, the survival of Borobudur’s site in the future willfully depends on its sustainable development policy.Keywords: Borobudur, saujana budaya, nilai ekonomi, sustainable development.